Probing the potential of salinity-tolerant endophytic bacteria to improve the growth of mungbean [Vigna radiata (L.) Wilczek] - Zahra, Syeda Tahseen; Tariq, Mohsin; Abdullah, Muhammad; Zafar, Marriam; Yasmeen, Tahira; Shahid, Muhammad Shafiq; Zaki, Haitham E. M.; Ali, Amanat (Frontiers in Microbiology, 2023)
Soil salinity is one of the major limiting factors in plant growth regulation. Salinity-tolerant endophytic bacteria (STEB) can be used to alleviate the negative effects of salinity and promote plant growth. In this study, thirteen endophytic bacteria were isolated from mungbean roots and tested for NaCl salt-tolerance up to 4%. Six bacterial isolates, TMB2, TMB3, TMB5, TMB6, TMB7 and TMB9, demonstrated the ability to tolerate salt. Plant growth-promoting properties such as phosphate solubilization, indole-3-acetic acid (IAA) production, nitrogen fixation, zinc solubilization, biofilm formation and hydrolytic enzyme production were tested in vitro under saline conditions. Eight bacterial isolates indicated phosphate solubilization potential ranging from 5.8–17.7 µg mL-1, wherein TMB6 was found most efficient. Ten bacterial isolates exhibited IAA production ranging from 0.3–2.1 µg mL-1, where TMB7 indicated the highest potential. All the bacterial isolates except TMB13 exhibited nitrogenase activity. Three isolates, TMB6, TMB7 and TMB9, were able to solubilize zinc on tris-minimal media. All isolates were capable of forming biofilm except TMB12 and TMB13. Only TMB2, TMB6 and TMB7 exhibited cellulase activity, while TMB2 and TMB7 exhibited pectinase production. Based on in vitro testing, six efficient STEB were selected and subjected to the further studies. 16S rRNA gene sequencing of efficient STEB revealed the maximum similarity between TMB2 and Rhizobium pusense, TMB3 and Agrobacterium leguminum, TMB5 and Achromobacter denitrificans, TMB6 and Pseudomonas extremorientalis, TMB7 and Bradyrhizobium japonicum and TMB9 and Serratia quinivorans. This is the first international report on the existence of A. leguminum, A. denitrificans, P. extremorientalis and S. quinivorans inside the roots of mungbean. Under controlled-conditions, inoculation of P. extremorientalis TMB6, B. japonicum TMB7 and S. quinivorans TMB9 exhibited maximum potential to increase plant growth parameters; specifically plant dry weight was increased by up to 52%, 61% and 45%, respectively. Inoculation of B. japonicum TMB7 displayed the highest potential to increase plant proline, glycine betaine and total soluble proteins contents by 77%, 78% and 64%, respectively, compared to control under saline conditions. It is suggested that the efficient STEB could be used as biofertilizers for mungbean crop productivity under saline conditions after field-testing.